Henna extract as a potential sacrificial agent in reducing surfactant adsorption on kaolinite: The role of salinity - Musa, M.S.M. (King Saud University, 2020)
The adsorption ability of henna extract as a cheap, environment-friendly and easily available sacrificial agent was investigated. Fourier transform infrared-attenuated total reflectance (FTIR-ATR) was used to characterized henna extract and kaolinite. The adsorption of henna extract on kaolinite was done using Ultravioletâvisible spectroscopy (UVâVis). The effects of salinity on the henna extract adsorption on kaolinite were studied. The mechanisms of the adsorption process were interpreted. Also, henna extract performances in reducing the adsorption of surfactant in the proximity of salts were assessed. The outcome shows that henna extract adsorption on kaolinite was increased with increasing salinity concentrations. The adsorption value increased from 7.88 to 13.35 mg/g in 0 and 50,000 mg/L of salinity respectively. The mechanisms involved in the adsorption process were mainly hydrogen bond, hydrophobic interactions, and electrostatic attractions. A reduction of 53 of surfactant adsorption was observed and showed a profound decrease in the adsorption of surfactant in the presence of henna extract suggesting a possibility to be utilized as a sacrificial agent in reducing surfactant adsorption. Â© 2019 The Authors